Supramolecular complexes of DNA with cationic polymers: The effect of polymer concentration. (25th April 2018) - Kondinskaia, Diana A.; Gurtovenko, Andrey A.
Abstract: Supramolecular complexes of DNA with cationic polymers are of tremendous importance as these polymers can successfully be used in gene therapy as delivery vectors of genetic material. In this work we employ atomistic molecular dynamics simulations to get an insight into the impact of polymer concentration on the structural and electrostatic properties of the complexes of DNA and cationic polymers. Four linear cationic polymers of different chemical structure and protonation state were studied: polyethylenimine (PEI), poly-l -lysine (PLL), polyvinylamine (PVA), and polyallylamine (PAA). For all considered polymers our computational findings clearly demonstrate that increasing the polymer concentration leads to the overcharging of the DNA molecule. This is relevant as the overall positive charge of the DNA-polycation complex is considered to be a prerequisite for efficient binding of the polyplexes to negatively charged cell membranes. However, the concentration effects themselves are found to be sensitive to the chemical structure of a polymer. In particular, flexible PEI chains, being characterized by the high affinity to DNA's phosphate groups, are able to bind to DNA in an independent manner. As a result, DNA and PEIs form compact complexes with the largest cumulative positive charge among all four types of cationic polymers under study. In contrast, PVA chains show the affinity to the major groove of DNA due to the hydrophobic nature of their backbones. This leads to stronger interactions with the DNA molecules and to the competition between PVA chains for DNA binding sites. This competition is responsible for the observed saturation in the PVA-induced neutralizing of the DNA charges when the PVA concentration increases. As for PLL and PAA, both these polycations are found to be less effective in neutralizing the charge of the polyanionic DNA molecules as compared to PEI and PVA. PLL has relatively long side chains, so that some of them cannot access DNA phosphates and reside in aqueous solution. In turn, PAA has a low protonation level, leading to a weak electrostatic binding to DNA. Overall, our findings can relate the properties of supramolecular DNA-polycation complexes at elevated polymer concentrations with the chemical structure of a polycation and therefore can be useful for the development of novel, highly efficient polycation-based delivery vectors of DNA. Graphical abstract: Image 1 Highlights: Atomistic computer simulations are employed to study DNA-polycation complexes. Four different types of cationic polymers are considered. The effects of polymer concentration on the complexes are explored. Increasing the polycation concentration leads to the overcharging of DNA. The concentration effects are sensitive to the chemical structure of polycations.